An Analysis on Learning Activity and Science Process Skills of High School Students through Guided Inquiry Physics Learning - Nur Diana (Universitas Muhammadiyah Makassar, 2019)
The research aimed to determine (1) learning activities of students of class XI IPA 4 in learning physics at SMAN 7 in Makassar. (2) activity of students of XI IPA 4 class through process skill at SMAN 7 in Makassar (3) science process skill in guided inquiry based physics learning activities of students of XI IPA 4 class at SMAN 7 in Makassar. This research was descriptive research using qualitative and quantitative approaches involving independent variables namely Guided Inquiry and the dependent variable was degree activity and science process skill. The population in this study were all students of the XI IPA class at SMAN 7 In Makassar with a sample selected in s XI IPA 4 class as an experimental class. The research instrument was used a test of science process skill in the form of multiple choices, observation sheets of student activities. The results of the analysis of learning activities students from 6 indicators that most students had activities in the active category. The Science Process Skill Analysis of students from 7 indicators that students were able to reach the indicators showing in the percentage results. The learning process will be effective if all teachers pay attention the students activities. So that learning became more varied and can train and developing the skill possessed by students.Keywords: Learning activities, skills of students, guided inquiryPenelitian ini bertujuan untuk mengetahui (1) aktivitas-aktivitas belajar peserta didik kelas XI IPA 4 dalam pembelajaran fisika di SMAN 7 Makassar. (2) aktivitas peserta didik kelas XI IPA 4 melalui keterampilan proses di SMAN 7 Makassar (3) keterampilan proses sains dalam pembelajaan fisika berbasis guided inquiry aktivitas peserta didik kelasXI IPA 4 SMAN 7 Makassar. Penelitian ini merupakan penelitian deskriftif dengan menggunakan Pendekatan kualitatif dan kuantitatif dengan melibatkan variabel bebas yaitu Guided Inquiry dan variabel terikat yaitu aktivitas belajat dan keterampilan proses sains. Populasi dalam penelitian ini adalah seluruh peserta didik kelas XI IPA SMA Negeri 7 Makassar dengan sampel di pilih kelas XI IPA 4 sebagai kelas eksperimen. Instrumen penelitian yang digunakan adalah tes ketarampilan proses sains dalam bentuk pilian ganda, lembar observasi aktivitas peserta didik.Hasil analisis aktivitas belajar peserta didik dari 6 indikator bahwa sebagian besar peserta didik memiliki aktivitas dalam kategori yang aktif. Analisis Keterampilan Proses Sains peserta didik dari 7 indikator bahwa peserta didik mampu mencapai indikator ditunjukan pada hasil persenatase. Proses pembelajaran akan menjadi efektif apabila semua guru bidang studi memperhatikan aktivitas peserta didik. Sehingga pembelajaran menjadi lebih bervariasi dan dapat melatih serta mengembangkan keterampilan- keterampilan yang dimiliki oleh peserta didik.Kata kunci: Aktivitas belajar, keterampilan peserta didik, guided inquiry